High-temperature corrosion mechanism of YSZ coatings subject to calcium–magnesium–aluminosilicate (CMAS) deposits: First-principles calculations - Zheng, Haizhong; Chen, Zheng; Li, Guifa; Shu, Xiaoyong; Peng, Ping (Corrosion science, 2017)
[Display omitted] •High-temperature corrosion process of CMAS/YSZ was investigated by DFT calculations.•CMAS bonded strongly with YSZ when it was in solid glass state, and diffused easily with YSZ when it was in liquid state.•The diffusion of (Ca↔Y) and (Si↔Y) induced YSZ depletion in yttrium, allowing tetragonal to monoclinic phase transition.•The cracking and peeling of the coating is attributed to the change of YSZ volume and the thermal stress. To study the degradation mechanism of yttria-stabilized zirconia (YSZ) coatings by CMAS glass attack at high temperature, density functional theory is used to calculate the energy of CMAS/YSZ(111) system. Over 1513K, the diffusion coefficients of atoms in CMAS are larger than those in YSZ (111) and the diffusion process of (Ca↔Y) and (Si↔Y) occurs, which induced to the formation of a sandwich structure and YSZ depleting in yttrium, allowing tetragonal to monoclinic phase transition of zirconia. The cracking and peeling off of the coating is attributed to the change of YSZ volume and the thermal stress.